Written Poetic Text for Children in Iraq and its Role in Child Nurture (Theoretical Study and Applied Reading in the Poetry of the Third Millennium) - Faisal, Anahed Naji; Alharthi, Jokha Mohammed (Dirasat: Human and Social Sciences, 2024)
Objectives: Shedding light on poetic text written for children in Iraq in the third millennium, and its role in child nurture, and making it an effective means for the child to know oneself their surroundings. Additionally, creating an educational environment with cognitive, perceptual, and psychological elements that takes into account the child’s cognitive system that relates to (stylistic,value-based and psychological) levels. Methods: The research adopts descriptive-analytical approach, which enables us to describe poetic texts written for children in Iraq in the third millennium. We have selected (sixteen poetic chants) from them as samples of the production of a group of poets, analyzing them and highlighting their role in raising their recipient (the child). Results: The important role of poetic text written for children in Iraq, especially in the third millennium, as one of the means of raising the child and developing him in terms of cognitive, intellectual, mental and mental health, within a societal framework that interacts with him and integrates with him, and through which he accepts others in an atmosphere of peaceful coexistence. Conclusion: The importance of examining educational nature of child’s literature in general and the poetic text written for children in particular as an important means of upbringing, with cognitive, perceptual and psychological elements, and a linguistic fabric that hides a culture and beliefs that the child grew up with and experienced Through it, the poet intends to caress the child’s thoughts in a way that ensures his participation, so he writes to his recipients in a way It gives him new ways to talk about, understand and express things.